The Legionella pneumophila effector DrrA is sufficient to stimulate SNARE-dependent membrane fusion - Arasaki, Kohei (2012)
The intracellular bacterial pathogen Legionella pneumophila subverts host membrane transport pathways to promote fusion of vesicles exiting the endoplasmic reticulum (ER) with the pathogen-containing vacuole. During infection there is non-canonical pairing of the SNARE protein Sec22b on ER-derived vesicles with plasma membrane (PM)-localized syntaxin proteins on the vacuole. We show that the L. pneumophila Rab1-targeting effector DrrA is sufficient to stimulate this non-canonical SNARE association and promote membrane fusion. DrrA activation of the Rab1 GTPase on PM-derived organelles stimulated the tethering of ER-derived vesicles with the PM-derived organelle resulting in vesicle fusion through the pairing of Sec22b with the PM syntaxin proteins. Thus, the effector protein DrrA stimulates a host membrane transport pathway that enables ER-derived vesicles to remodel a PM-derived organelle, suggesting that Rab1 activation at the PM is sufficient to promote the recruitment and fusion of ER-derived vesicles.